Influence of process temperature and residence time on the manufacturing of amorphous solid dispersions in hot melt extrusion. (16th March 2022) - Gottschalk, Tobias; Grönniger, B.; Ludwig, E.; Wolbert, F.; Feuerbach, T.; Sadowski, G.; Thommes, M.
Abstract: The manufacturing of amorphous solid dispersions via hot melt extrusion is a topic of high interest in pharmaceutical development. By this technique, the drug is dissolved in the molten polymer above solubility temperature within the process time. In this study, an experimental framework is proposed determining the minimum required process temperature and the residence time using particularly low quantities of material. Drug/polymer mixtures in different ratios were processed in a micro-scale extruder while the process temperature and residence time were varied systematically. The phase situation was assessed by the turbidity of the final extrudate. Four different drug/polymer mixtures were investigated in three drug/polymer ratios. The minimum required process temperature was close to solubility temperature for each specific formulation. Moreover, an influence of residence time on the phase situation was found. About three minutes were required in order to dissolve the drug in the polymer at these process conditions.